2015
DOI: 10.3390/s150407206
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Stress Analysis of Metal Oxide Films for CMOS-Integrated Gas Sensors

Abstract: The integration of gas sensor components into smart phones, tablets and wrist watches will revolutionize the environmental health and safety industry by providing individuals the ability to detect harmful chemicals and pollutants in the environment using always-on hand-held or wearable devices. Metal oxide gas sensors rely on changes in their electrical conductance due to the interaction of the oxide with a surrounding gas. These sensors have been extensively studied in the hopes that they will provide full ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 57 publications
(52 reference statements)
0
44
1
Order By: Relevance
“…Thus results in an overall decrease or increase in the metal oxide resistance [95]. According to Filipovic et al In 2 O 3 and ZnO based metal oxide materials can be used as gas sensors, when heated to temperatures between 250 C and 550 C [95]. But present investigation revealed that InZnO materials exhibited gas sensor response even at room temperature.…”
Section: Gas Sensors Behaviormentioning
confidence: 52%
See 1 more Smart Citation
“…Thus results in an overall decrease or increase in the metal oxide resistance [95]. According to Filipovic et al In 2 O 3 and ZnO based metal oxide materials can be used as gas sensors, when heated to temperatures between 250 C and 550 C [95]. But present investigation revealed that InZnO materials exhibited gas sensor response even at room temperature.…”
Section: Gas Sensors Behaviormentioning
confidence: 52%
“…At higher temperatures, oxygen is adsorbed at the metal oxide surface by trapping electrons from the bulk material. Thus results in an overall decrease or increase in the metal oxide resistance [95]. According to Filipovic et al In 2 O 3 and ZnO based metal oxide materials can be used as gas sensors, when heated to temperatures between 250 C and 550 C [95].…”
Section: Gas Sensors Behaviormentioning
confidence: 99%
“…5 (c) it can be inferred that the WO 3 film surface is rough and porous with the formation of some agglomerates around 5-10 m wide. Various open pores could be seen which is advantageous for the diffusion of gases in the bulk of the film [55]. The total WO 3 deposition area on the gold electrodes was 97.5 mm 2 .…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…At increased temperatures, oxygen is adsorbed at the metal oxide surface by trapping electrons from the bulk material [16]. The result is the formation of a depletion layer at the surface and an overall decrease or increase in the metal oxide resistance, depending on whether the material is n-type or p-type, respectively.…”
Section: B Metal Oxide Sensor Operationmentioning
confidence: 99%